Victimization by traditional bullying and cyberbullying and the combination of these among adolescents in 13 European and Asian countries - Chudal Roshan; Tiiri Elina; Klomek Anat Brunstein; Ong Say How; Fossum Sturla; Kaneko Hitoshi; Kolaitis Gerasimos; Lesinskiene Sigita; Li Liping; Huong Mai Nguyen; Praharaj Samir Kumar; Sillanmäki Lauri; et al. (Springer, 2022)
There has been a lack of studies on bullying in non-western low-income and middle-income countries. This study reported the prevalence of traditional victimization, cybervictimization, and the combination of these, in 13 European and Asian countries, and explored how psychiatric symptoms were associated with victimization. The data for this cross-sectional, school-based study of 21,688 adolescents aged 13-15 were collected from 2011 to 2017. The main outcomes were traditional and cybervictimization obtained from student self-reports. The Strengths and Difficulties Questionnaire was used to assess psychiatric symptoms. Generalized estimating equation and logistic regression models were used to estimate odds ratios (ORs) and 95% confidence intervals (95% CIs). The mean prevalence of any victimization was 28.9%, of traditional victimization only, this was 17.7%, and for cybervictimization only this was 5.1%. Cybervictimization occurred both independently, and in combination with, traditional victimization. The mean prevalence of combined victimization was 6.1%. The mean proportion of those who were cyberbullied only among those who were either cyberbullied only or bullied both traditionally and in cyber was 45.1%. The rates of prevalence varied widely between countries. In the total sample, those who experienced combined victimization, reported the highest internalizing symptoms (girls, OR 1.25, 95% CI 1.22-1.29; boys, OR 1.29, 95% CI 1.25-1.33). The study findings suggest that anti-bullying interventions should include mental health components and target both traditional and cyberbullying. Due to the overlap between these, targeting bullying should primarily focus on how to reduce bullying behavior rather than just focusing on where bullying takes place.